Kamase-Mase Value In The Pa’bitte Passapu Dance Performance of Kajang Ethnic Group of Bulukumba Regency, South Sulawesi - Astuti, Andi Arie; Hartono, Hartono; Cahyono, Agus (Universitas Negeri Semarang, 2019)
The Pa’bitte Passapu dance is one of the artistic heritages of the Kajangethnic group which is not well known yet by other people. The Kajangethnic group is anethnic group which is obedient to the content of pasang or a message called tallasa kamase-mase or simple life. Based on this background, the researcher focuses the research on the performance process and the kamase-mase value on the Passapu Pa’bitte dance performance. This study aims to analyze and describe the performance process and the kamase-mase value on the Passapu Pa’bitte dance. The method used in this study is qualitative with an interdisciplinary approach. Data collection techniques used are observation, interview, and document study. The validity technique used is triangulation, and the data analysis is done by reducing data, presenting data and drawing conclusions to obtain research data. The results of the study performance that the kamase-mase value in the Pa'bittePassapu dance performance still follows the rules in pasang (message), namely tallasa kamase-mase (simple life) contained in the clothing of dancers and musicians, the property of dancers and musicians, and the performance process the dance itself. The implication of this Pa’bitte Passapu Dance research for the Kajangethnic group is to preserve the Pa’bitte Passapu dance as an entertainment dance that still holds the rules that apply to the Kajang ethnic group.